Structure-microwave absorption performance correlations of GNPs/ZnO nanocomposite absorber: Synthesis, characteration and mechanism investigation. Issue 10 (July 2019) - Zhang, Weidong; Zheng, Yuan; Zhang, Xue; Zhu, Qing; Tian, Lili; Wu, Hongjing; Yan, Hongxia; Qi, Shuhua
Abstract: Graphene nanoplatelets (GNPs) based materials are promising and low-cost absorbers. To develop new varieties of these absorbers, two kinds of GNPs/ZnO nanocomposites (GNPs/ZnO nanorod arrays and GNPs/ZnO nanoneedles) were synthesized in this paper, and the microwave absorption performance (MAP) together with the relevant mechanism were investigated based on the different microstructures, followed by the discussion of the growth mechanism of ZnO nanorod and nanoneedle. The result reveals that GNPs/ZnO nanorod arrays have strong reflection loss (RL) up to −44.8 dB, and effective attenuation bandwidth (RL˂-10 dB) of 4.65 GHz. While, GNPs/ZnO nanoneedles possess effective attenuation bandwidth of 6.7 GHz that covered entire X-band, and the superb RL was −15.3 dB. According to the detail analysis, we found that the pathways of attenuation EM wave are the same, and the differences between each other are responsible for the different intensity of interface polarization and multiple-scattering, due to the different microstructures.